Flow field and heat transfer characteristics in dimple pipe with different shape of dimples - Sajida Lafta Ghashim (Wasit Journal of Engineering Sciences)
In this work, a numerical study of a thermal performance of water flow inside a dimpled pipe. The effect of three types of dimples (circular, square and rhombus) studied in the numerical simulation. A commercial program called ANSYS was used to model the flow through a circular pipe .The three-dimensional governing differential equations of mass, momentum, and energy were used together with the (K − ε ) model to evaluate the impact of dimples on a turbulent flow and the velocity field. The study was carried out in the Reynolds number (Re) range (2500–15000). The research results demonstrate that the presence of a dimple on the pipe surface greatly increases the rate of heat transmission and the friction factor compared to a normal smooth pipe. Also, the numerical study demonstrated that the Nusselt number (Nu) in case of circular  dimples  at diameter  (4 , 6 and 8) mm was (22, 28 and 43) % greater than the smooth surface.  It is discovered that the improved pipe with circular dimples have a benefit for increased heat transmission efficiency compared with the square and rhombus dimples. Additionally , circular dimples have the ability to supply the lowest friction factor (f) when compared to other types of dimple. The pipe with circular dimples with D= 4mm , at Reynolds number 2500 provided the largest thermal performance criterion (PEC) value about 1.44.